Comparison of the Video Game Functional Assessment-Revised (VGFA-R) and Internet Gaming Disorder Test (IGD-20) - Sprong, Matthew Evan; Griffiths, Mark D.; Lloyd, Daniel Perry; Paul, Erina; Buono, Frank D. (Frontiers in Psychology, 2019)
Research related to problematic video gaming has increased during the previous decade and instruments to assess Internet Gaming Disorder (IGD) using DSM-5 criteria have been established. The purpose of the study was to compare the four functions of the Video Game Functional Assessment-Revised (VGFA-R) (i.e., attention, escape, tangible, sensory stimulation) and the six core components of the 20-item Internet Gaming Disorder Test (IGD-20) (i.e., salience, mood modification, tolerance, withdrawal symptoms, conflict, and relapse). Method: The sample comprised 304 US gamers (mean age of 29.8 years; female 58.55%) who completed an online survey. A Confirmatory Factor Analysis was performed to assess the relationship between the functions of the VGFA-R and the factors of the IGD scale. Results: Findings indicated a high significant correlation between the two instruments and that the six IGD criteria were most correlated with escape (all six correlations above .53). The CFA for the VGFA-R was estimated with maximum likelihood (ML) estimation. Chi-square statistic goodness-of-fit test, χ2(34, N=304) = 271.64, p < .0001; χ2/df = 7.99; CFI = .88; RMSEA = .15, (90% confidence interval [CI]; .14, .17). All factor loadings were significant (ranging from 5.30 to 6.63), and there was no evidence of cross-loading for any indicator. Conclusions: The findings confirm previous research showing that escape is often one of the key motivating factors among those experiencing problematic video gaming. Given the two instruments were designed in completely different ways for different purposes, the fact that they are so highly correlated suggests that the VGFA-R could be used by clinicians and practitioners as an adjunct to the IGD-20 and provide extra information relating to the motivations underlying the problematic gaming among their clients.